The genetic prehistory of the Baltic Sea region - Alissa Mittnik (Nature Portfolio, 2018)
The population history of Europe is complex and its very north has not yet been comprehensively studied at a genetic level. Here, Mittnik et al. report genome-wide data from 38 ancient individuals from the Eastern Baltic, Russia and Scandinavia to analyse gene flow throughout the Mesolithic and Bronze Age.